Clinical predictors of chronic rhinosinusitis: do the Canadian clinical practice guidelines for acute and chronic rhinosinusitis predict CT-confirmation of disease? - Paige Moore; Brian Blakley; Eric Meen (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The diagnosis of chronic rhinosinusitis (CRS) based on clinical presentation alone remains challenging. To improve the accuracy of clinical diagnosis, the Canadian Rhinosinusitis Guidelines recommend the use of specific symptom and endoscopic criteria. Our study objective was to determine whether symptom and endoscopic criteria, as defined by the Canadian Rhinosinusitis Guidelines, accurately predict CT-confirmed CRS diagnosis. Methods A retrospective cohort study of 126 patients who underwent CT sinuses based on clinical suspicion of possible CRS. The presence of symptom and endoscopic criteria, as defined by the Canadian Rhinosinusitis Guidelines, were compared between patients with and without a CT-confirmed CRS diagnosis using two-tailed Fisher’s exact tests. Positive predictive values and likelihood ratios were determined for each symptom and endoscopic finding. Results Overall, 56.3% of patients had a CT-confirmed diagnosis of CRS. With the exception of nasal polyps, none of the symptom or endoscopic criteria had a statistically significant correlation with positive CT sinuses. For symptom criteria, positive predictive values ranged from 52.4% to 63.4%; likelihood ratios ranged from 0.85 to 1.34. For endoscopic criteria, positive predictive values and likelihood ratios were 71.4% and 1.94 (edema); 63.0% and 1.32 (discharge); and 92.9% and 10.1 (nasal polyps). 35.2% of patients with CT-confirmed CRS had normal endoscopic exams. Conclusion The Canadian Rhinosinusitis Guidelines’ symptom and endoscopic criteria for CRS, with the exception of nasal polyps on endoscopy, do not accurately predict CT-confirmed disease. In addition, a normal endoscopic exam does not rule out CRS.